2015
DOI: 10.1007/s10803-015-2373-1
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Peer-Related Social Competence Interventions for Children with Autism Spectrum Disorder: A Meta-Analysis and Descriptive Review of Single Case Research Design Studies

Abstract: The purpose of this review was to critically examine and summarize the impact of school-based interventions designed to facilitate the peer-related social competence of children with autism spectrum disorder (ASD). Reviewed studies employed a single-case experimental design, targeted peer-related social competence, included children 3-12 years old with an ASD, and took place in school settings. Articles were analyzed descriptively and using the evaluative method to determine study quality. Additionally, effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 76 publications
(150 reference statements)
2
71
0
1
Order By: Relevance
“…However, group processes should be considered as well. Focusing on group processes rather than on individual characteristics has been a promising approach regarding the development and evaluation of interventions to foster social interactions among pupils with and without SEN (Whalon et al, 2015). Indeed, facilitating social participation requires the effort and engagement of all, including peers and teachers (Farmer, McAuliffe Lines, & Hamm, 2011;Garrote, Sermier Dessemontet, & Moser Opitz, 2017;Gest & Rodkin, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, group processes should be considered as well. Focusing on group processes rather than on individual characteristics has been a promising approach regarding the development and evaluation of interventions to foster social interactions among pupils with and without SEN (Whalon et al, 2015). Indeed, facilitating social participation requires the effort and engagement of all, including peers and teachers (Farmer, McAuliffe Lines, & Hamm, 2011;Garrote, Sermier Dessemontet, & Moser Opitz, 2017;Gest & Rodkin, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, pupils with autism spectrum disorders (ASD) have difficulties with self-oriented social skills, such as initiating social interactions, which places them more at risk of being socially isolated (Bellini et al, 2007). However, intervention studies have demonstrated that these children can benefit from the supportive behaviour of their TD peers with respect to the development of social interaction skills (Camargo et al, 2014;Whalon, Conroy, Martinez, & Werch, 2015). In addition, engaging in other-oriented social skills, such as cooperative and prosocial behaviour, can also have a positive impact on the social participation of pupils with ASD (Kamps et al, 2002).…”
Section: Social Skills Of Pupils With Senmentioning
confidence: 99%
“…Several reviews of research that employed this model have found a high percentage of effectiveness (Watkins et al, 2015; Whalon et al, 2015), although with different intensities. Chan et al (2009) found positive results in 91% of the 42 studies reviewed, with students aged 2–13 years, although these authors advise interpreting the results with caution, given the limitations in the fidelity of the implementation, as classmates, rather than professionals, applied the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Research into ADHD in adolescents has primarily focused on the use of medication and behaviour treatments aiming to improve behaviour as interventions for students with ADHD, particularly a combination of the two (Miranda , Jarque & Tarraga, 2006;Raggi & Chronis, 2006), as this is the predominant choice of intervention for this age group (Young & Amarasinghe, 2010). Similarly, Cognitive-Behavioural Interventions focusing on core social difficulties by improving social skills through the use of promting/reinforcement, modelling, role-playing, and/or verbal or manual guidance have been identified as the predominant interventions for children and adolescents with AS (Volker & Lopata, 2008;Whalon et al, 2015). As such, school-based interventions for adolescents with neuropsychiatric disabilities often concentrate on improving academicperformance by targeting the functional manifestation of children's and adolescents' core problems, i.e., attention, impulsiveness and hyperactivity control and social interaction (Miranda et al, 2006;Richardson et al, 2015;Volker & Lopata, 2008;Young & Amarasinghe, 2010).…”
Section: Students With Neuropsychiatric Disabilities and Support In Smentioning
confidence: 99%